2005
DOI: 10.1002/ddr.20046
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease, estrogens, and clinical trials: a case study in drug development for complex disorders

Abstract: Alzheimer's disease (AD) is the most prevalent neurodegenerative disorder, affecting more than 4 million Americans, and it is a huge drain on health care resources. Moreover, the cost burden of AD will increase substantially without the development of drugs that prevent its onset or slow its progression. At the present time, the available AD drugs provide, at best, temporary cognitive improvement, and costbenefit analyses indicate no more than marginal support for their use. AD is a disorder of complex etiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 325 publications
(240 reference statements)
0
6
0
Order By: Relevance
“…Their outcome has been extensively commented upon in the recent literature and has brought many fundamental issues of hormone therapies to light, but discussions were mainly limited to the effects of estrogens (1)(2)(3)(4)(5). In fact, progestagens are generally only considered with respect to their usefulness in preventing uterine hyperplasia and malignancy in response to estrogens.…”
Section: Introductionmentioning
confidence: 98%
“…Their outcome has been extensively commented upon in the recent literature and has brought many fundamental issues of hormone therapies to light, but discussions were mainly limited to the effects of estrogens (1)(2)(3)(4)(5). In fact, progestagens are generally only considered with respect to their usefulness in preventing uterine hyperplasia and malignancy in response to estrogens.…”
Section: Introductionmentioning
confidence: 98%
“…The Women’s Health Initiative clinical trials have revealed improved cognition (Howell et al, 2006; Maki and Henderson 2012), although they relied on conjugated equine estrogen instead of E2, the main human estrogen, used in most basic science investigations. However, adverse side effects of the currently available estrogen therapies such as an increased incidence of breast cancer and circulatory system impacts, have been well known (Rossouw et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dating back to the 1990s, MitoKor was one of the most significant early ventures to focus on mitochondrial approaches to treating and diagnosing disease-no doubt ahead of its time, at least in our biased view (e.g., see Howell et al [2005], , Moos et al [2008Moos et al [ , 2009, and Pei et al [2003aPei et al [ , 2003b). A wealth of knowledge regarding mitochondrial targets, structures, and disease has accumulated in the interim.…”
Section: Apoptosis and Abt-737 Ion Channels And Diazoxide Krebs Cyclementioning
confidence: 99%